Analisis Perubahan Perilaku Konsumen E-Commerce Shopee Pada Masa Pandemi Covid 19 Di Kota Bandung - Silalahi, Friska; Harmon Chaniago (International Journal Administration, Business & Organization, 2021)
Currently (2021), the world is being hit by the COVID-19 pandemic. Almost all sectors are affected, not only health. Restrictions on community activities have an effect on business activities which in turn have an impact on the economy. because of that all started using digital media to carry out their activities. Likewise, fulfilling daily needs as much as possible is done online which causes changes in consumer behavior in e-commerce. This study aims to determine whether there has been a change in consumer behavior, and how the behavior of Shopee consumers changed during the Covid 19 pandemic in Bandung. The research method used is descriptive method and quantitative approach. By using survey research by distributing questionnaires. This study found 5 factors that influence changes in shopee consumer behavior in Bandung, Indonesia